Association of Cutaneous Lupus Manifestations with Neurological and Pulmonary Involvement in Systemic Lupus Erythematosus - Nighat Fatima, Ubaid Ullah Ansari, Shoaib Saleem Khan, Kashif Sardar, Bakhtawar Farooq, Zahid Habib Qureshi (Pakistan Journal of Medical & Health Sciences, 2024)
Background: SLE is a chronic multi-system autoimmune disorder. Common cutaneous manifestations that can be indicative of systemic immune activity. Neurologic and pulmonary complications have clinical significance because they are associated with morbidity, delay in diagnosis and long-term disability. Objective: The aim of this study was to assess the correlation between the skin manifestations of lupus and neurological and pulmonary involvement in patients with systemic lupus erythematosus (SLE). Methods: This observational cross-sectional study was conducted at Multan Medical and Dental College, Multan, Pakistan, from September 2022 to September 2023. Non-probability consecutive sampling was used to include 150 SLE patients. The cutaneous manifestation, neurological involvement and pulmonary involvement were evaluated by clinical history, physical examination, laboratory record, imaging findings, and specialist assessment as needed. Data was analysed with SPSS. Chi-square or Fisher exact test was used to test associations and p-values <0.05 were deemed significant. Results: Patients had a mean age of 31.6 ± 9.4 years, and 126 patients were female. The most common cutaneous manifestations were photosensitivity, malar rash, alopecia, oral ulcers, discoid rash, vasculitic lesions, and livedo reticularis. Neurological involvement was present in 46 patients, while pulmonary involvement was present in 39 patients. Neurological and pulmonary involvement were significantly associated with vasculitic lesions, livedo reticularis, oral ulcers and photosensitivity. The strongest associations with both systemic complications were seen with vasculitic lesions. Conclusion: Cutaneous lupus manifestations, particularly vasculitic lesions, livedo reticularis, oral ulcers, and photosensitivity, may indicate increased risk of neurological and pulmonary involvement in systemic lupus erythematosus. Sensitive skin inspection can be helpful in early systemic evaluation and timely multidisciplinary management. Keywords: Systemic lupus erythematosus; cutaneous lupus; neurological involvement; pulmonary involvement; vasculitic lesions.